FEATURES OF THE LEXICON OF THE KIRIMCHAK LANGUAGE (Web of Teachers: Inderscience Research, 2024)
Kirimchaks are the Turkic people of Judaism. The Krymchak language belongs to the Kipchak-Polovtsian subgroup of Turkic languages. Therefore, it is natural that this language has differences or common features with other Kipchak languages. In this article, the author tried to analyze the Krymchak language through the prism of the Kipchak dialects of the Uzbek language. This language shows its differences from other languages through its own layer and acquired words. At the same time, the Kipchak dialect of the Uzbek language, comparing it, was able to provide important conclusions.